Effect of Plasma Uric Acid on Antioxidant Capacity, Oxidative Stress, and Insulin Sensitivity in Obese Subjects - Fabbrini, Elisa; Serafini, Mauro; Colic Baric, Irena; Hazen, Stanley L.; Klein, Samuel (Diabetes (New York, N.Y.), 2014)
Oxidative stress is purported to be involved in the pathogenesis of obesity-associated insulin resistance. We evaluated whether alterations in levels of circulating uric acid (UA), a systemic antioxidant, affects the following: 1) systemic (plasma and saliva) nonenzymatic antioxidant capacity (NEAC); 2) markers of systemic (urinary 8-iso-prostaglandin-F2α) and muscle (carbonylated protein content) oxidative stress; and 3) whole-body insulin sensitivity (percentage increase in glucose uptake during a hyperinsulinemic-euglycemic clamp procedure). Thirty-one obese subjects (BMI 37.1 ± 0.7 kg/m2) with either high serum UA (HUA; 7.1 ± 0.4 mg/dL; n = 15) or normal serum UA (NUA; 4.5 ± 0.2 mg/dL; n = 16) levels were studied; 13 subjects with HUA levels were studied again after reduction of serum UA levels to 0 by infusing a recombinant urate oxidase. HUA subjects had 20–90% greater NEAC, but lower insulin sensitivity (40%) and levels of markers of oxidative stress (30%) than subjects in the NUA group (all P < 0.05). Acute UA reduction caused a 45–95% decrease in NEAC and a 25–40% increase in levels of systemic and muscle markers of oxidative stress (all P < 0.05), but did not affect insulin sensitivity (from 168 ± 25% to 156 ± 17%, P = NS). These results demonstrate that circulating UA is a major antioxidant and might help protect against free-radical oxidative damage. However, oxidative stress is not a major determinant of insulin action in vivo.